Uji Efektivitas Antihiperglikemik Ekstrak Etanol Bunga Rosella (Hibiscus sabdariffa L) yang di Induksi Sukrosa pada mencit Jantan (Mus musculus) - Abdulkadir, Widy Susanti; Akuba, Juliyanty; Rahman, Muh. Nadzirul; Damiti, Sukmawati (Madu : Jurnal Kesehatan, 2024)
Diabetes mellitus is a serious condition characterized by an increase in glucose levels (GDS) ≥ 200 mg/dL due to the body’s inability to produce the hormone insulin effectively. Many plants have antidiabetic properties, including the roselle (Hibiscus sabdariffa L.) flower, which has been rarely studied scientifically. This research aims to determine the most effective dose of ethanol extract of roselle flower for antihyperglycemic activity in male mice induced with a 90% sucrose solution. This research employs the Oral Sucrose Tolerance Test (OSTT) method. Activity tests in mice were conducted on 5 treatment groups: Group I was the negative control (Na-CMC 1% w/v), Group II was the positive control (acarbose), Group III received ethanol extract at a dose of 250 mg/kgBW, Group IV received ethanol extract at dose of 500 mg/kgBW, and Group V received ethanol extract at a dose of 750